2017
DOI: 10.1155/2017/1850256
|View full text |Cite
|
Sign up to set email alerts
|

Urethral Reconstruction Using Mesothelial Cell-Seeded Autogenous Granulation Tissue Tube: An Experimental Study in Male Rabbits

Abstract: Objective. This study was to evaluate the utility of the compound graft for tubularized urethroplasty by seeding mesothelial cells onto autogenous granulation tissue. Methods. Silastic tubes were implanted subcutaneously in 18 male rabbits, of which nine underwent omentum biopsies simultaneously for in vitro expansion of mesothelial cells. The granulation tissue covering the tubes was harvested 2 weeks after operation. Mesothelial cells were seeded onto and cocultured with the tissue for 7 days. A pendulous ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Moreover, it was shown that the detected transitional epithelial cells in the treated urethral defect areas were originated from implanted epidermal cells (keratinocytes) suggesting that the urethral environment may have directed transformation of implanted keratinocytes into transitional epithelial cells [75]. Recently a similar finding in supporting the regenerative capability of cell-seeded tubularised silastic graft in treating long urethral stricture was also reported by Jiang et al [12] in 2017.…”
Section: Grafting Strategies Using Tissue Engineered Urethramentioning
confidence: 52%
See 2 more Smart Citations
“…Moreover, it was shown that the detected transitional epithelial cells in the treated urethral defect areas were originated from implanted epidermal cells (keratinocytes) suggesting that the urethral environment may have directed transformation of implanted keratinocytes into transitional epithelial cells [75]. Recently a similar finding in supporting the regenerative capability of cell-seeded tubularised silastic graft in treating long urethral stricture was also reported by Jiang et al [12] in 2017.…”
Section: Grafting Strategies Using Tissue Engineered Urethramentioning
confidence: 52%
“…Six months post-operation, the results revealed development of continuous epithelial layer and organized smooth muscle bundles with no evidence of urethral stricture in animals receiving seeded tubularized graft as opposed to control group, which was treated, by unseeded tubularized graft. Also severe fibrosis and progressive shrinkage were only observed in unseeded grafts [12].…”
Section: Progenitor Cellsmentioning
confidence: 96%
See 1 more Smart Citation
“…The urethral lumen in the control group was severely contracted, whereas in the experimental group wide urethral calibers were observed. Moreover, the newly formed urothelium replaced the mesothelium 4 weeks post-implantation 29 .…”
Section: Resultsmentioning
confidence: 97%
“…Urethral reconstruction techniques also include the use of buccal mucosa graft; engineered tissue grafts are being investigated as novel management modalities. These include mesothelial cell-seeded autogenous granulation tissue tube and cell-based tissue engineering approach [23,24]. Ansari and Karram reported female urethral reconstruction for complete urethral loss using acellular porcine urinary bladder matrix with successful clinical outcomes [25].…”
Section: Discussionmentioning
confidence: 99%